Exploring geothermal resources with the CSAMT and microtremor methods: a case study in Tangquan, Jiangsu Province, China - Xu, Hao; Yang, Xiaodong; Cai, Xiangyang; Xu, Ziqiao; Liao, Shengzhu; Wu, Xiaoping (Frontiers in Earth Science, 2024)
The development of geothermal energy has received extensive attention because of global energy scarcity and environmental pollution. The Tangquan area is in the north of the Yangtze fold belt, and the lack of magmatic rock development has resulted in a low-temperature type of geothermal reservoir. There are sporadic hot springs and cold springs exposed in the study area, but the lack of detailed exploration data, uncertain deep geological structure, and unknown geothermal reservoir formation mechanism seriously restrict the exploration and development of geothermal resources in the area. Filling underground faults with water can significantly reduce electrical resistivity, while traps filled with warm water can cause a decrease in S-wave velocity. Thus, a new integrated geophysical method includes the controlled source audio-frequency magnetotelluric (CSAMT) and microtremor is applied for geothermal exploration in the region. The combination of CSAMT and microtremor methods can determine thermal-controlled and water-conducting structures more effectively and locate geothermal storage more accurately. With geophysical and geological data, the source, channel, storage, and cover of regional geothermal reservoir formation are analyzed. That is, the regional NE-and NW-trending faults are explained as thermal-controlled and water-conducted structures, respectively. The deep Sinian Dengying Formation supplies a heat-and water-bearing space. It is found that the tectonic intersection area, especially the tensional fault zone, is closely related to the existence of geothermal reservoirs, which is well verified by later drilling results. A geothermal reservoir model is finally established to comprehensively understand the distribution of geothermal energy in the region.